WHEN THE ENEMY IS NOT HIDING: A CASE OF SEVERE CUSHING’S SYNDROME SECONDARY TO ACTH-SECRETING NASAL PARAGANGLIOMA - Low, Chee Koon; Ng, Yoke Mui; Krishnan, Gayathri Devi; Redzuan, Shazatul Reza Mohd; Rani, Nor Haizura Abd; Alias, Azmi; Rajoo, Subashini; Bidin, Mohamed Badrulnizam Long (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE Ectopic secretion of ACTH is often an endocrine emergency because of its intensity of hypercortisolism. Only 5% of paragangliomas of the head and neck region are hormonally active. A 35-year-old Malaysian female developed a generalized seizure. She had Cushingoid features with profound hypokalemia and hyperglycemia. She had elevated levels of morning cortisol (12,136 nmol/L, >19 times elevated) and 24-hour urine cortisol (71,442.6 nmol/day, >60 times elevated), unsuppressed cortisol following overnight dexamethasone test, and elevated ACTH (49.9 pmol/L). Imaging studies revealed a locally invasive sinonasal tumour extending into the cranium with bilateral adrenal gland hyperplasia. Ketoconazole and metyrapone combination therapy failed to control hypercortisolemia. Etomidate infusion was then started preoperatively in preparation for bilateral adrenalectomy. Tumour resection was performed successfully via endoscopic and transcranial approaches. Pathological examination confirmed neuroendocrine tumour cells of low Ki-67 proliferative index with positive staining for ACTH.